Spine Metastasis: Patients With Poor Performance Status (ECOG) Could benefit From Palliative Surgical Care! A Prospective Cohort Study. Issue 7 (1st April 2023) - Amelot, Aymeric; Terrier, Louis-Marie; Le Nail, Louis-Romée; Buffenoir, Kévin; Cook, Ann-Rose; François, Patrick; Marie-Hardy, Laura; Mathon, Bertrand
Abstract : Study Design: This study used a French prospective national multi-center database of patients with spine metastasis (SpM). Objective: The main challenge was to clarify if SpM patients presenting poor ECOG-PS could benefit from a surgical intervention. Background: Spine metastases (SpM) are debilitating lesions commonly found in the evolution of cancer. At present, patients with poor ECOG-PS do not benefit from surgical care. Materials and Methods: Between 2014 and 2017, 176 SpM patients with poor initial ECOG-PS (3 or 4) were identified. Results: The median overall survival of patients was 2.1 months (SD 0.2). Seventy-one patients (40.3%) underwent surgery: for 49 patients (27.8%) the intervention consisted of a simple decompression and for 22 patients (12.5%) the previous was associated with an osteosynthesis. Patients who underwent surgery demonstrated significantly longer median overall survival than those who did not: 3.5 months (SD 0.4) versus 1.6 (SD 0.2) ( P <0.0001). No significant differences between operated/nonoperated patients were noted concerning median age (66.4 vs. 64.2 y, P =0.897), the median number of SpM (4.1 vs. 4.2, P =0.374), ECOG-PS 4 ratio (41.6 vs. 39.3%, P =0.616), or for primary tumors ( P =0.103). Patients who underwent surgery statistically improved their neurological impairment according to the Frankel score: 5/11 (45.4%) from A to C, 5/17 (29.4%) from B to C or D, 6/11 (54.5%) from C to D and 2/4 (50%). Twelve patients (16.9%) presented a postoperative complication. Conclusion: Patients with poor ECOG-PS could benefit from surgery. Even though survival gain is small, it permits the preservation of their neurological function. By making ambulation possible, pain is decreased during the last months of their lives.